Return to Sport and Return to Self-Reported Preinjury Level After Surgical Repair of Acute Achilles Tendon Rupture: A 2-Year Prospective Cohort Analysis - Maxime Guerot; Frederic Khiami; Eugénie Valentin; Olivier Grimaud; Mohamad K. Moussa; Antoine Gerometta; Alain Meyer; Nicolas Lefèvre; Alexandre Hardy (Journal of Clinical Medicine, 2026)
Background: Achilles tendon ruptures are among the most common sports injuries. The literature reports highly variable “return to sport” (RTS) rates depending on the study, as the definition of return to play is not consistent. Our purpose was to assess RTS and self-reported relative performance level after surgical management of acute Achilles tendon ruptures. Method: In this retrospective analysis of a prospective cohort, the RTS rate and the return to self-reported preinjury level (RTPIL) in patients treated surgically for acute Achilles tendon rupture between November 2020 and September 2023 with at least 2 years of follow-up were reported. The primary outcomes were the RTS and RTPIL rates at last follow-up. Secondary outcomes were Patient-Reported Outcome Measures (PROMS): Achilles Tendon Total Rupture Score (ATRS), Ankle Ligament Reconstruction–Return to Sport after Injury (ALR-RSI), Foot and Ankle Ability Measure (FAAM), Tegner Activity Scale (TAS) and the University of California and Los Angeles (UCLA) activity level rating scale. Data was collected preoperatively; at three, six, twelve, and twenty-four months postoperatively; and then every two months thereafter. Kaplan–Meier analysis was performed to measure time to RTS and RTPIL. Results: In the final analysis, 65 patients were included for analysis of RTS and RTPIL, and 69 for the PROMS. In total, 81.7% (58) were male, and the mean age was 40.6 years (SD 12.5). The RTS rate was 76.9%, and the RTPIL rate was 44.6%. The mean delay to RTS was 11.6 months (SD 7.6). The median time to RTS was approximately 14 months (95% CI, 10.0–18.0). The RTPIL rate continued to increase between the first and second years after surgery. At the last follow-up, the median ATRS was 89 with an interquartile range (IQR) of [77.0–95.0], ALR-RSI was 80 [62.5–95.0], FAAM activity was 91.7 [85.7–97.6], FAAM sport was 85.9 [68.8–96.9], TAS was 7 [5–7], and UCLA was 10 [9–10]. Median follow-up was 24.8 months. Conclusions: In conclusion, self-reporting of RTS and RTPIL yields low rates, and caution should be used in overly optimistic preoperative counselling. Level of evidence: IV.